PERAN TEKNOLOGI PENDIDIKAN DALAM PENGGUNAAN E-LEARNING SEBAGAI PLATFORM PEMBELAJARAN DIMASA PANDEMI C0VID-19 - Asih Setiyowati; Unik Hanifah Salsabila; Rida Zulaika; Virandra Adhe Arista; Yoga Wahyu Santoso (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
The COVID-19 pandemic has caused quite a stir in various sectors, including the economic, health, socio-cultural and evan education sectors. Various government policies issued, one of which is online learning, is an effort to prevent the spread of COVID-19, especially in the school environment, considering that schools are a dense element consisting of millions of people spread across Indonesia. Technology as a forum for implementing bold learning plays an important role, therefore researchers examine the role of e-learning in learning during the COVID-19 pandemic. With the research method, the research paper tries to examine whether this provides efficiency.